Encapsulação de nanopartículas de magnetita em matriz de poli(metacrilato de metilacoácido metacrílico) por processo de polimerização em miniemulsão - Nunes, Juliana de Souza (2007)
Magnetic particles are systems with potential use in drug delivery systems, ferrofluids, and effluent treatment. In many situations, such as in biomedical applications, it is necessary to cover magnetic particles with an organic material, as polymers. In this work, magnetic particles were obtained through covering magnetite particles with poly(methyl methacrylate‐comethacrylic acid) via miniemulsion polymerization process. The resultant materials were characterized X‐ray diffraction (XRD), Fourier Transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), zeta potential () measurements and vibrating sample magnetometry (VSM). XRD results showed magnetite as the predominant cristalline phase in all samples and that cristallites had nanometric dimensions. Thermogravimetric analysis revealed an increase in polymer thermal stability as a result of magnetite encapsulation. TGA results showed also that the encapsulation efficiency was directly related to nanoparticles s hidrofobicity degree. VSM measurements showed that magnetic polymeric particles were superparamagnetic, so that they may be potentially used for magnetic (bio)separation